2003
DOI: 10.21236/ada462282
|View full text |Cite
|
Sign up to set email alerts
|

User Guide for Characterizing Particulate Matter. Evaluation of Several Real-Time Methods. Appendix 1

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…Continuous particle-bound PAHs were measured at 1minute intervals with EcoChem (League City, TX) PAS-2000 analyzers with PM 1.0 inlets at the fixed sites to investigate if this measurement was of use in identifying woodsmoke PM. This method is a semi-quantitative measurement of total particle-bound PAHs (Wilson et al, 1995), since the response depends on the kinds of PAHs present in the sample (Kelly et al, 2003). Ultraviolet light from a 222-nm excimer lamp ionizes particle-bound PAH molecules, and an electric field then removes the free electrons.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous particle-bound PAHs were measured at 1minute intervals with EcoChem (League City, TX) PAS-2000 analyzers with PM 1.0 inlets at the fixed sites to investigate if this measurement was of use in identifying woodsmoke PM. This method is a semi-quantitative measurement of total particle-bound PAHs (Wilson et al, 1995), since the response depends on the kinds of PAHs present in the sample (Kelly et al, 2003). Ultraviolet light from a 222-nm excimer lamp ionizes particle-bound PAH molecules, and an electric field then removes the free electrons.…”
Section: Methodsmentioning
confidence: 99%
“…The single particle aerosol mass spectrometer (SPAMS) offers real-time detection of atmospheric particles and can simultaneously provide information on the size distribution, number concentration, and chemical composition of the particles at a single particle level. This information can be collated to a direct source apportionment based on single particle number concentration and chemical composition (Kelly et al, 2003). Only a limited number of studies thus far have verified high-resolution online measurements against the traditional offline analysis; for example, compared major ions (sulfate, nitrate, and ammonium) measured in filter samples against those measured online by a monitor for aerosols and gases in ambient air (MARGA) system, and the two sets of data showed agreement within 25%.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of ATOFMS over other methods of source apportionment is its ability to identify associations among chemical species within individual particles. This association can be related directly to source apportionment (Kelly et al, 2003). However, the key disadvantages are the cost of instrument purchase, and interpretation of the spectra which requires a steep learning curve (Kelly et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This association can be related directly to source apportionment (Kelly et al, 2003). However, the key disadvantages are the cost of instrument purchase, and interpretation of the spectra which requires a steep learning curve (Kelly et al, 2003). The deployment of ATOFMS for both outdoor and indoor pollution studies has been widely reported in published work (Held et al, 2002;2007;2008;2012;Gross et al, 2000;Healy et al, 2013;Smyth et al, 2013).…”
Section: Introductionmentioning
confidence: 99%